Engineering protein theranostics using bio-orthogonal asparaginyl peptide ligases - Wang, Zhen (2021)
Background: Protein theranostics integrate both diagnostic and treatment functions on a single disease-targeting protein. However, the preparation of these multimodal agents remains a major challenge. Ideally, conventional recombinant proteins should be used as starting materials for modification with the desired detection and therapeutic functionalities, but simple chemical strategies that allow the introduction of two different modifications into a protein in a site-specific manner are not currently available. We recently discovered two highly efficient peptide ligases, namely butelase-1 and VyPAL2. Although both ligate at asparaginyl peptide bonds, these two enzymes are bio-orthogonal with distinguishable substrate specificities, which can be exploited to introduce distinct modifications onto a protein.